MONITOR OF THE STUDENT’S PHYSICAL CULTURE FORMATION - Shodiyev Ergashali Kudratshoevich (Galaxy International Interdisciplinary Research Journal, 2023)
The development of monitoring of the formation of physical culture of a student based on the use of a complex of diagnostic methods provides a comprehensive and comprehensive study of the characteristics of the formation of physical culture of subjects. different outlook, activity and cognitive conditions. A detailed analysis of various aspects of the learning process helps to adjust the learning process in time.